2020
DOI: 10.1038/s41598-020-78474-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of clozapine-related metabolic disturbances with CYP3A4 expression in patients with schizophrenia

Abstract: Clozapine is effective in treatment-resistant schizophrenia; however, adverse effects often result in discontinuation of clozapine therapy. Many of the side-effects are associated with pharmacokinetic variations; therefore, the expression of major clozapine-metabolizing enzymes (CYP1A2, CYP3A4) in patients may predict development of adverse effects. In patients with schizophrenia (N = 96), development of clozapine concentration-dependent metabolic side-effects was found to be associated with pharmacokinetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19]. Despite the fact that Menus et al [61] found no association between CYP1A2 expression and any ADR, some variants have been formerly linked to tardive dyskinesia [91,92] and to an increased risk of insulin and lipid elevation [93].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19]. Despite the fact that Menus et al [61] found no association between CYP1A2 expression and any ADR, some variants have been formerly linked to tardive dyskinesia [91,92] and to an increased risk of insulin and lipid elevation [93].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Menus et al [61], exaggerated clozapine concentrations (>600 ng/mL) were more frequently noted in low CYP3A4 expressers (22%) than in normal/high expressers (2.7%) (low vs. normal/high expressers: OR = 9.8 (95% CI 1.8-55.0), p = 0.009). They also noted an association between norclozapine formation and CYP3A4 expression (0.56 ± 0.17 vs. 0.98 ± 0.62, p < 0.0001).…”
Section: Main Implications Of Cytochromes Genotypingmentioning
confidence: 90%
See 3 more Smart Citations